“lustitia Christi”: Dimensiones personalistas y existencialistas de la Justificación en la VIª sesión del Concilio de Trento - Bouzas, Francisco Martínez (Estudio agustiniano, 2011)
In this essay, following the outline of the dimensions of the person- al and existential thing in today’s culture, the author goes back to the Sixth Session of the Council of Trent to investigate the extent to which personal and existential thought patterns were present, or framed the ideas, in discus- sions of the decree of justification. In this first part, the research focuses on discussions and actions of parents and theologians about the first draft decree (‘Cum tuba coeli’). It discusses the “official thinking” and the inter- ventions of those speakers, especially Seripando, supporters of personalistic formulations that took into account the justifying process of existential man of flesh and bone.